Differential resistance to cell entry by porcine endogenous retrovirus subgroup A in rodent species - Mattiuzzo, Giada (BioMed Central, 2007)
BACKGROUND: The risk of zoonotic infection by porcine endogenous retroviruses (PERV) has been highlighted in the context of pig-to-human xenotransplantation. The use of receptors for cell entry often determines the host range of retroviruses. A human-tropic PERV subgroup, PERV-A, can enter human cells through either of two homologous multitransmembrane proteins, huPAR-1 and huPAR-2. Here, we characterised human PARs and their homologues in the PERV-A resistant rodent species, mouse and rat (muPAR and ratPAR, respectively). RESULTS: Upon exogenous expression in PERV-A resistant cells, human and rat PARs, but not muPAR, conferred PERV-A sensitivity. Exogenously expressed ratPAR binds PERV-A Env and allows PERV-A infection with equivalent efficiency to that of huPAR-1. Endogenous ratPAR expression in rat cell lines appeared to be too low for PERV-A infection. In contrast, the presence of Pro at position 109 in muPAR was identified to be the determinant for PERV-A resistance. Pro109. was shown to be located in the second extracellular loop (ECL2) and affected PERV-A Env binding to PAR molecules. CONCLUSION: The basis of resistance to PERV-A infection in two rodent species is different. Identification of a single a.a. mutation in muPAR, which is responsible for mouse cell resistance to PERV-A highlighted the importance of ECL-2 for the viral receptor function.